Analisis Daya Tampung Beban Pencemaran Air Sungai Asam Kota Jambi - Ridho Renaldi; Marhadi Marhadi; Anggrika Riyanti (Universitas Batanghari Jambi, 2021)
The Asam River is one of the rivers that crosses the sub-districts, including Kota Baru, Jelutung and Pasar Jambi. Asam River is located in Jambi City with a length of 10.68 km, and a watershed area of 2,930 Ha. The Asam River is generally polluted by waste originating from activities, office areas, hotels, trade centers, prominent figures and residential areas. To determine the quality of acid river water, it is necessary to analyze the load carrying capacity of water pollution. Methods that can be used to analyze the load carrying capacity of water pollution include the Mass Balance method and the Streeter-Phelps method. Based on the results of the calculation of the carrying capacity of the river pollution load using the mass balance method on the parameters, pH, TSS, BOD and COD. The Asam River which cannot accommodate the pollution load is found in the TSS parameter of -110.129 mg/l with a quality standard of 30 mg/l according to the Ministry of Environment and Forestry Number P.68 of 2016 concerning domestic waste quality standards, while for the parameters pH, BOD, and COD still below the domestic waste quality standard. The results of the calculation of the carrying capacity of the pollution load using the streeter-phelps method show that at 4 sampling points the BOD concentration can still accommodate the pollution load in the river which does not exceed the quality standard. the effect of DO concentration on AP1 Upstream to AP4 Downstream is still available in sufficient amount of DO.